The Role of Parenting to Increase Gross and Fine Motor Skills Development in Children Aged 5-6 Years - I Gusti Ayu Putu Satya Laksmi; Ni Made Nopita Wati; R. Tri Rahyuning Lestari (Universitas Muhammadiyah Semarang, 2020)
Children's development includes several aspects including aspects of motor development, cognitive, social-emotional, language, moral, religion. One of the factors that influence motor development is parenting. The purpose of this study was to determine the relationship between parenting parents with gross motor and fine motor development in children aged 5-6 years. This study used a quantitative non-experimental correlational type research design with a cross-sectional approach. The sample consisted of 75 respondents using a non-probability sampling technique with purposive sampling. the majority of parents applying democratic parenting, as many as 69 people (92%), most children aged 5-6 years have appropriate motor development, as many as 65 people (86.6%), most children aged 5-6 years have appropriate fine motor development, as many as 72 people (96%), there is a strong relationship between parenting parents with gross motor development in children aged 5-6 years with a correlation coefficient (r) = 0.628, there is a strong relationship between patterns foster parents with fine motor development in children aged 5-6 years with a correlation coefficient (r) = 0.672. The results of this study are expected to be used as a guide for parents who have not applied democratic parenting to their children so that the child's motor development can grow optimally.